Heritage of oneness - Ramphal, Shridath S. (Commonwealth Secretariat LondonGB, 1988)
Retraces pathways that brought Africans and Indians to British Guiana. Describes life on plantation Vreed-en-Hoop and other plantations of Guyana's coastland and uses this to analyse the social, cultural, economic, and political experiences the immigrants suffered under slavery and indentureship. Reviews the struggle for emancipation. Outlines lessons to be learned by the Guyanese people from their common history of slavery, indenture and colonialism. These include the importance of national cohesion, the primacy of educational development, the eradication of servitude, racism, intolerance, oppression, authoritarianism, and the honest admission and correction of past mistakes.